Executive stock options plans and its effect on short-run corporate performance - Ismail Zuriadah, Mahjom Nurhanie, Hashim Emilda, (Universiti Pendidikan Sultan Idris, 2016)
Executive stock options plans and its effect on short-run corporate performance by Ismail Zuriadah, Mahjom Nurhanie, Hashim Emilda,